The Foundation and the First Years of Odessa State University Existence - V. O. Kuznetsov (History of science and technology, 2013)
Odessa State university foundation peculiarities and the first years of its existence were studied on the base of the State Odessa Region Archive materials and the materials of N.A. Savchuk’s family archive.